Effect of the milling method and particle structure on the color tone of (Cr, Fe)2O3 inorganic black masterbatch pigment - Aslan, Emre; Bulut, Melis; Grijalbo, Alejandro; cicek, Bugra (ELSEVIER, 2022)
(Cr, Fe)2O3 pigment was milled using different techniques into the same particle sizes to investigate the influence of milling processes on its properties. The research showed that milling type resulted in significant color differences, accompanied by the pigment color changing from intense reddish-brown to dark brown. Differences in the morphology of the particles embedded in the plastic matrix led to different light scattering, which is observed as a decrease in the color saturation of the pigment. Particle size distribution (PSD) was characterized by measuring with a laser diffraction particle size analyzer. Pigments were milled down to 4 mm in all milling methods. The very small particles in the pigment affected the light scattering and the color tone. The particle size of the pigment milled by the planetary mill was D10 = 0.035 l +/- 0.1. Color values of the plastic plates were measured according to CIE laboratory analysis. The pigment milled with the planetary mill was lighter, greener, and yellower (DL*=4.15, Da*=3.68, Db*=2.96). The pigment milled with the jet-mill was closest to the pigment color after calcination. The pigment milled with ball mill was slightly greener than the values after calcination (Da*=1). (c) 2022 The Society of Powder Technology Japan. Published by Elsevier B.V. and The Society of Powder Technology Japan. All rights reserved.
Keywords: Jet mill; Ball mill; Particle structure; Particle size; Planetary milling; SIZE; SEDIMENTATION; AGGREGATION; DIOXIDE; Engineering